SIMPLE ESTIMATION AIR TEMPERATURE FROM MODIS LST IN GIFU CITY, JAPAN - Ali Rahmat (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2017)
In the developing country or poor country difficult to access meteorological data such as air temperature, it's caused by the limitation of equipment or funding. Air temperature is one of the meteorological data commonly used to predict evaporation or to understanding climatic condition in a specific location. Nowadays from satellite data can estimate some meteorological data. But the detail of explanations about how to get and how to use satellite data is limited and difficult to adopt for beginners. This paper explains how to get MODIS LST data to estimate air temperature data study case in Gifu City, Japan. The results show data from MODIS LST is higher than data from the local meteorological station for day time and lower for night time, but still can use because the pattern is similar. Mean of maximum air temperature and minimum air temperature can be used as daily average air temperature. MOD11A2 product data was better than MYD11A2 data to predict air temperature. MODIS LST data can be used for untouched areas like desert or forest.